Screening for resistance to cowpea aphid (Aphis craccivora koch) in wild and cultivated cowpea (Vigna unguiculata L. walp.) accessions - Souleymane, A.; Akenova, M.E.; Fatokun, C.A.; Alabi, Y. (2013)
Cowpea aphid (Aphis craccivora Koch) is a major pest of cowpea (Vigna unguiculata L. Walp.) particularly in the drier regions of the tropics. Although aphid resistant varieties had been developed, resistance has recently broken down. The present study seeks to identify new sources of resistance. 105 cowpea cultivars and 92 wild cowpea accessions were screened in a greenhouse for resistance to cowpea aphid. The results revealed that Among the cowpea cultivars only IT97K-556-6 showed some level of tolerance as 40 % of the seedlings survived until 21 days after infestation even with a high aphid population. The cultivar TVu 1659 had the highest number of aphids per seedling with 59.0 and 268.0 at 9 and 13 days after infestation, respectively while the wild cowpea accession TVNu 1158 had the lowest number of aphids per seedling with 3.2, 11.0 and 25.0 at 5, 9 and 13 days after infestation, respectively. Apart from having the lowest number of aphids 80% of the seedlings of this wild cowpea line survived to 21 days after infestation. The wild cowpea line TVNu 1158 was consistently aphid resistant and should be a good source of resistance genes for incorporation into cultivated cowpea.